2020
DOI: 10.1063/5.0008310
|View full text |Cite
|
Sign up to set email alerts
|

Current methodologies and approaches for the formation of core–sheath polymer fibers for biomedical applications

Abstract: The application of polymer fibers has rocketed to unimaginable heights in recent years and occupies every corner of our day-to-day life, from knitted protective textile clothes to buzzing smartphone electronics. Polymer fibers could be obtained from natural and synthetic polymers at a length scale from the nanometer to micrometer range. These fibers could be formed into different configurations such as single, core-sheath, hollow, blended, or composite according to human needs. Of these several conformations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 185 publications
(229 reference statements)
0
37
0
Order By: Relevance
“…The electrospun bers can be applied in biomedicine, pharmacy, food, water treatment, air purication, energy electronics and information engineering. [12][13][14][15][16][17][18][19][20][21] The electrospun bers can be fabricated using natural polymer or synthetic polymer as the main substrate materials and the appropriate solvents based on these different elds. The preparation process shows a greater deal of autonomy and plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…The electrospun bers can be applied in biomedicine, pharmacy, food, water treatment, air purication, energy electronics and information engineering. [12][13][14][15][16][17][18][19][20][21] The electrospun bers can be fabricated using natural polymer or synthetic polymer as the main substrate materials and the appropriate solvents based on these different elds. The preparation process shows a greater deal of autonomy and plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…The former would generate fiber deformation in axial direction showing with a reversible stretching process, while the latter would make the fiber waggle in a direction perpendicular to the axis or rotate in angles based on the fiber's cross‐section center. [ 51,52 ] It was shown that due to the confinement of microchannel and fixing sites, the fiber exhibited discernible stretching and retracting almost at the axial direction according to the contraction and relaxation cycles of living cardiomyocytes. The optical detection was observed by a fiber optic spectrometer, whose optic probe was focused on the 10% site of the structural color segment.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the heterogeneous structural color microfibers could realize single‐cell‐level sensing with a sensitivity at the µN scale, similar to the microfiber‐based cardiac force detection. [ 51 ] Although a sensitivity gap with single‐cell detection methods, such as AFM (reach to 10 pN), [ 8 ] TFM (around nN) [ 11 ] and elastomeric microarrays (around nN), [ 13 ] still exists, the sensitivity of this heterogeneous microfiber could be further improved by series of optimizations. The unique feature of the force–optical visible transformation of these microfibers would greatly simplify the complexity and reduce the expenditure of the whole detection system.…”
Section: Resultsmentioning
confidence: 99%
“…copper nanoparticles, whilst the core of the fibres can be a strong polymer which imparts the strength and toughens the mask. This requires upscaling mass production to suit, and work has already been carried out to achieve this [ 16 , 17 ]. However, in parallel, existing respirators and masks need upgrading to properly inhibit the entry of viral particles, and as with Covid-19, these can be smaller than 100nm.…”
Section: Materials and Technologiesmentioning
confidence: 99%